2006
DOI: 10.1007/s00125-006-0388-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase p85α regulatory subunit gene PIK3R1 haplotype is associated with body fat and serum leptin in a female twin population

Abstract: Aims/hypothesis Phosphatidylinositol 3-kinase (PI3K) couples the leptin and insulin signalling pathways via the insulin receptor substrates IRS1 and IRS2. Hence, defective activation of PI3K could be a novel mechanism of peripheral leptin or insulin resistance. We investigated associations of tagging single-nucleotide polymorphisms (tSNPs) in the PI3K p85α regulatory subunit gene PIK3R1 with anthropometry, leptin, body fat and insulin sensitivity in a female twin population of European extraction. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
4
16
1
Order By: Relevance
“…Others have attempted to evaluate gene-wide association with insulin resistance -related phenotypes or biomarkers using selected sets of tagging single nucleotide polymorphisms, and reported inconsistent results (21 -24). In a large female twin study of eight selected tagging single nucleotide polymorphisms, Jamshidi et al found associations between other single nucleotide polymorphisms in PIK3R1 with serum leptin levels, body fat, and other measures of insulin resistance, but reported no association for the Met326Ile variant (21). An earlier Danish study of 380 young healthy subjects reported a significant association of this variant with insulin sensitivity (22), but the same research group failed to replicate that association in a subsequent study (23).…”
Section: Discussionmentioning
confidence: 99%
“…Others have attempted to evaluate gene-wide association with insulin resistance -related phenotypes or biomarkers using selected sets of tagging single nucleotide polymorphisms, and reported inconsistent results (21 -24). In a large female twin study of eight selected tagging single nucleotide polymorphisms, Jamshidi et al found associations between other single nucleotide polymorphisms in PIK3R1 with serum leptin levels, body fat, and other measures of insulin resistance, but reported no association for the Met326Ile variant (21). An earlier Danish study of 380 young healthy subjects reported a significant association of this variant with insulin sensitivity (22), but the same research group failed to replicate that association in a subsequent study (23).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, defective activation of PI3K could be a novel mechanism of peripheral leptin or IR. The association of the PI3KR1 SNPrs1550805 with serum leptin and body fat may reflect a diminished capability of PI3K to signal via IRS-1 or IRS-2 in response to leptin (Jamshidi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Described in present study results provide the first evidence for association of SNPs in UTRs of INSR and PIKR1 genes with genes expression rates. So far, all investigated in these genes SNPs were localized mainly in coding regions (Kusari et al, 1991;Baynes et al, 2000;Almind et al, 2002;Jamshidi et al, 2006;Højlund et al, 2006). Presented results stand for the first report where evaluation of SNPs in UTRs of INSR and PIK3R1 genes with gene expression levels was performed in peripheral lymphocytes and adipose tissues.…”
Section: Discussionmentioning
confidence: 90%